Análise da paisagem e emissões de gases efeito estufa em reservatórios do estado de São Paulo - Oliveira-Andreoli, Erica Zanardo (Universidade Federal de São Carlos, 2023)
Reservoirs are transition ecosystems designed for their multiple uses, such as energy production, water supply, irrigation, and fishing. Despite hydroelectric power being considered as clean energy, studies dating from the end of the last century reported the possibility that reservoirs have a high potential for the emission of Greenhouse Gases (GHG). In addition to the change in carbon cycling due to water impoundment, the reservoir interacts with the watershed, which undergo constant changes in their land uses and cover. Therefore, the objective was to evaluate GHG emissions in the reservoirs of Barra Bonita (agricultural profile – intensive monoculture of sugarcane), Itupararanga (conservation profile) and Jaguari-Jacareí (agricultural profile – pasture) and to analyze the integrity and multifunctionality of the landscape in its areas of influence. To carry out the landscape analysis, it was necessary to survey land use and cover in the pre- and post-damming period (i.e., 2010 and 2020), using geoprocessing software and the R language, to obtain the Distance to Nature index (D2N). The survey of GHG emissions was carried out using the G-res tool, developed by the International Hydropower Association (IHA). The application of the D2N index showed that, despite the increase in non-agricultural uses in the areas of influence, there was an increase in the amount of natural areas and a reduction in areas in more artificial conditions during the entire period in the three profiles. Regarding the application of the G-res tool, all reservoirs acted as CO2 sinks in the pre-damming period (between -324 tCO2e/year and -5.191 tCO2e/year) and emitted a small amount of CH4 in the same period (between 39 tCO2e/year and 159 tCO2e/year). In the post-damming period, all reservoirs started to emit GHG (between 10.137 tCO2e/year and 210.268 tCO2e/year). The use of the D2N index and the G-res tool are essential in understanding the spatial dynamics of landscapes, in addition to providing better planning of public policies.
Landscape analysis and greenhouse gas emissions in reservoirs in the state of São Paulo
Keywords: Reservatórios artificiais; Gases efeito estufa; G-res tool; Bacias hidrográficas; Análise da paisagem; Uso e cobertura da terra; Reservoirs; Greenhouse Gases; Watersheds; Landscape analysis; Land use and land cover; CIENCIAS BIOLOGICAS::ECOLOGIA; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL::CONSERVACAO DA NATUREZA::CONSERVACAO DE BACIAS HIDROGRAFICAS; OUTROS::CIENCIAS